(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The goal of this work is research and development of light sources suitable for use in hospitals, nursing homes, hospices and other similar institutions. During the day spectral power distribution (SPD) of this type luminaire needs to simulate natural day light that affects the natural circadian rhythm of humans. Maintaining the natural circadian rhythm impacts positive on human health, improves mood, prevents the development of depression and helps to overcome them. In the late afternoon increase light in the red-orange part. Light of this kind of spectral composition doesn’t inhibit melatonin production and the human body naturally prepares for rest and sleep. At night artificial lighting should be in the red - orange area to enable patients to sleep and staff to fulfill their obligations. Theoretical analysis and selection of suitable LEDs for the realization of the luminaire with the desired characteristics are made. Performed experimental studies make possible achieving the desired characteristics of light and appropriate LEDs’ modes of operation.